Medical-Grade Honey as an Alternative Treatment for Antibiotics in Non-Healing Wounds-A Prospective Case Series - Adéla Holubová; Lucie Chlupáčová; Lada Cetlová; Niels A. J. Cremers; Andrea Pokorná (MDPI AG, 2021)
Non-healing wounds are usually colonised by various types of bacteria. An alternative to antibiotic treatment in patients with infected wounds with local signs of inflammation may be medical-grade honey (MGH), which favourably affects the healing process with its antimicrobial, antioxidant, anti-inflammatory, and immunomodulatory properties. The objective of this study was to evaluate the effect of MGH therapy on the healing process of non-healing wounds of various aetiologies and different wound colonisations. Prospective, observation-intervention case studies (n = 9) of patients with wounds of various aetiologies (venous leg ulcers, diabetic foot ulcers, surgical wound dehiscence) are presented. All wounds were treated with MGH and the healing trajectory was rigorously and objectively monitored. In all cases, pain, odour, and exudation were quickly resolved, which led to an improvement in the quality of life of patients. Despite the proven bacterial microflora in wounds, antibiotic treatment was not necessary. The effects of MGH alleviated the signs of local infection until their complete elimination. In eight out of nine cases, the non-healing wound was completely healed. MGH has antimicrobial, anti-inflammatory, and antioxidant effects in wounds of various aetiologies and forms an effective alternative for the use of antibiotics for treating locally infected wounds.